Direct oral anticoagulants in patients with chronic thromboembolic pulmonary hypertension and the presence of recent thrombus during pulmonary endarterectomy. (19th July 2022) - Jeong, Ina; Alotaibi, Mona; Fernandes, Timothy M.; Kim, Suhyun; Kerr, Kim M.; Yang, Jenny; Pretorius, Victor; Madani, Michael; Kim, Nick H.
Abstract: Patients with chronic thromboembolic pulmonary hypertension (CTEPH) require lifelong anticoagulant therapy. The safety and efficacy of direct oral anticoagulant (DOAC) in the chronic and transitional management of CTEPH has not been investigated. We performed a retrospective analysis of 405 consecutive pulmonary endarterectomy (PEA) cases at the University of California, San Diego, from July 2015 through July 2017. PEA specimen was reviewed for the presence of acute or subacute thrombotic material distinct from the expected chronic disease removed at the time of PEA by two investigators blinded to the patient information. Of 405 PEA cases, 166 patients (41.0%) were anticoagulated with one of three available DOACs; 239 (59.0%) presented on either oral vitamin‐K antagonist or chronic injectable therapy. There were no significant differences in baseline characteristics between DOAC and non‐DOAC groups. Evidence of recent thrombus was observed in 22 (13.3%) in the DOAC group versus 16 (6.7%) within the non‐DOAC group. The odds ratio of DOACs usage and evidence of recent thrombus was 2.34 (95% confidence interval: 1.1–5.0, p = 0.03) after adjusting for age, gender, race, body mass index, and history of antiphospholipid antibody syndrome. CTEPH patients referred for PEA while on DOAC therapy were twice as likely to have associated acute or subacute thrombi present at the time of surgery compared with those on more traditional, non‐DOAC anticoagulant therapies. This raises questions of the safety and efficacy of DOACs in the chronic management of CTEPH.